PEMBERIAN CAMPURAN AMELIORAN (KAPUR KALSIT, PUPUK HIJAU KRINYUH DAN BATUAN FOSFAT ALAM) PADA BEBERAPA VARIETAS PADI GOGO (Oryza sativa L.) DI TANAH ULTISOL - Jessica Stephanie; Idwar '; Islan ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research to investigated influence of ameliorant mixture (calsite lime, krinyuh green manure and natural rock phosphate) toward some varieties upland rice on Ultisol soil and get the best ameliorant mixture for increase the productivity of upland rice. Research conducted in BiologicalControl Community (Biccom) field, (UPT) research farm in Faculty of Agriculture, Riau University on Bina Widya Campus Km 12,5 Simpang BaruSub-district, Tampan District, Pekanbaru from December 2014 till May 2015. This research arranged experimentally using Completely Randomized Design Factorials consist of 3 levels varieties: Inpago 8, Situ Patenggang and Situ Bagenditand 5 levels ameliorants mixture : K0 (without ameliorant mixture), K1 (24,99 lime g+krinyuh green manure 12,49 g/polybag), K2 (lime 24,99 g + BFA 12,49 g/polybag), K3 (krinyuh green manure 12,49 g+BFA12,49 g/polybag) and K4 (lime 24,99 g+krinyuh green manure 12,49 g+BFA 12,49 g/polybag) and then obtained 15 experimental units with 3 sample each unit. Parameter observed of plant height, maximum tillering amount, flowering time, penicle length, productive tillering amount, harvest time, 1000 grain weight, percentage of grain pithy, dried grain weight, weight dry straw plant and ratio of grain and straw. Resultsanalysis of variancefollowed by Duncantest at 5%. Theresults ofthis research concluded givingmixtureameliorantexhibitdifferentresponsestovarietiesInpago8, Situ PatenggangandSitu Bagenditand allobservationparameters. Givingmixtureameliorant green manure krinyuh12,49g+BFA12,49g/polybag can usedas an ameliorantonUltisoltoincreasegrowthand production ofupland rice. Keywords : ameliorant mixture, upland rice, ultisol soil.